Proceedings of the National Scientific Students’ Conference "Chemistry and Chemical Technology 2019" - Tumkevičius, Sigitas; Inkrataitė, Greta; Daumantas, Liudas (Vilnius University Proceedings, 2019)
Scientific Committee: Prof. A. Beganskienė, VU Doc./Assoc. Prof. J. Dodonova, VU Prof. V. Getautis, KTU Prof. S. Grigalevičius, KTU Doc./Assoc. Prof. T. Paulauskienė, KU Prof. S. Tumkevičius, VU Prof. A. Žukauskaitė, KU Organizers: Prof. S. Tumkevičius (Chairman), VU G. Inkrataitė (secretary), VU Dr. R. Vaitkus, VU Dr. S. Višniakova, VU I. Gabriūnaitė, VU L. Sinušaitė, VU M. Steponavičiūtė, VU M. Vagner, VU O. Safinas, VU SA L. Daumantas, VU